2008
DOI: 10.2217/14796694.4.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Trial Assessing Individualized Options for Treatment for Breast Cancer: The TAILORx Trial

Abstract: Novel genetic profiling tests of breast cancer tissue have been shown to be prognostic for overall survival and predictive of local and distant rates of recurrence in breast cancer patients. One of these tests, Oncotype DXtrade mark, is a diagnostic test comprised of a 21-gene assay applied to paraffin-embedded breast cancer tissue, which allows physicians to predict subgroups of hormone-receptor-positive, node-negative patients who may benefit from hormonal therapy alone or require adjuvant chemotherapy to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 48 publications
0
62
0
2
Order By: Relevance
“…The mRNAs selected for this assay place most weight on the ER and HER2 signaling pathways. The ability of Oncotype DX to guide treatment selection is formally being evaluated in the TAILORx clinical trial [Zujewski and Kamin, 2008].…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNAs selected for this assay place most weight on the ER and HER2 signaling pathways. The ability of Oncotype DX to guide treatment selection is formally being evaluated in the TAILORx clinical trial [Zujewski and Kamin, 2008].…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
“…It is encouraging to see the emergence of large clinical trials for some breast cancer predictive tests; the Oncotype DX test (TAILORx, [Zujewski and Kamin, 2008]) and the MammaPrint test (MINDACT, [Cardoso et al 2008]). However, the design of these trials may not allow direct conclusions to be drawn about the clinical usefulness of these tests [Koscielny, 2008].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Oncotype DX is suggested by the American Society of Clinical Oncology and the National Comprehensive Cancer Network for the decision of adjuvant chemotherapy in ER-positive, node-negative breast cancer patients [70,71] . Tailor X is a large prospective randomized trial set to validate OncotypeDx in clinical practice by better defining the intermediate risk stratum [72] .…”
mentioning
confidence: 99%
“…The benefit in the intermediate risk category is less clear. Arguably, the Oncotype dx test is not yet informative for those cases; results of the tailorx study are awaited 9 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the correlations of ng overall, tf, np, and mc with rs risk group in this patient population, all patients with er-positive, her2-negative, T1-2, N0 breast cancer who were referred to the bcca during 2007-2011 and were known to have had an Oncotype dx test performed on clinical study 9,10 were identified (n = 226). Histologic grading was assessed on the specimen used for the Oncotype dx test.…”
Section: Methodsmentioning
confidence: 99%